Mental Health First Aid guidelines for helping a suicidal person: a Delphi consensus study in Japan - Colucci, Erminia (BioMed Central, 2011)
BACKGROUND: This study aimed to develop guidelines for how a member of the Japanese public should provide mental health first aid to a person who is suicidal. METHODS: The guidelines were produced by developing a questionnaire containing possible first aid actions and asking an expert panel of 32 Japanese mental health professionals to rate whether each action should be included in the guidelines. The content of the questionnaire was based on a systematic search of the relevant evidence and claims made by authors of consumer and carer guides and websites. The panel members were asked to complete the questionnaire by web survey. Three rounds of the rating were carried and, at the end of each round, items that reached the consensus criterion were selected for inclusion in the guidelines. During the first round, panel members were also asked to suggest any additional actions that were not covered in the original questionnaire (to include items that are relevant to local cultural circumstances, values, and social norms). Responses to these open-ended questions were used to generate new items. RESULTS: The output from the Delphi process was a set of agreed upon action statements. The Delphi process started with 138 statements, 38 new items were written based on suggestions from panel members and, of these 176 items, 56 met the consensus criterion. These statements were used to develop the guidelines appended to this article. CONCLUSIONS: There are a number of actions that are considered to be useful for members of the Japanese public when they encounter someone who is experiencing suicidal thoughts or engaging in suicidal behaviour. Although the guidelines are designed for members of the public, they may also be helpful to health professionals working in health and welfare settings who do not have clinical mental health training.